Pengembangan Media Berbasis Video Blog (Vlog) Kearifan Lokal Keragaman Budaya Di Kabupaten Bangka - Jihan Rafiadilla; Maharani Oktavia; Puji Ayurachmawati (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2023)
This study aims to produce video blog (vlog) based media development products on local wisdom of cultural diversity in Bangka Regency that meet valid and practical criteria. This research uses the type of development research (research and development). The development model in this study refers to the ADDIE model which consists of the analyze stage, the design stage, the development stage, the implementation stage and the evaluation stage. The subject of this research is class IV SD Negeri 08 Sungailiat. The research data were obtained from validation questionnaires and student response questionnaires. The results of the study were based on the team's expert validation questionnaire which assessed in terms of media appearance, presentation of material and use of language as a whole, obtaining a percentage score of 92.7% in the category of very valid and suitable for use at the trial stage. The results of the One To One questionnaire totaling 4 students obtained a percentage score of 94.6% in the very practical category and the results of the Small Group questionnaire consisting of 12 students obtained a percentage score of 94.0% in the very practical category. Based on the results developed by researchers entitled development of video blog (vlog) based media on local wisdom of cultural diversity in Bangka Regency, it is concluded that video blog (vlog) based media has been developed that meets valid and practical criteria.